Chitosan functionalized by citric acid: an efficient catalyst for one-pot synthesis of 2, 4-diamino-5H-[1]benzopyrano[2, 3-b]pyridine-3-carbonitriles 5-(arylthio) or 5-[(arylmethyl)thio] substituted. (4th May 2017) - Safaei-Ghomi, Javad; Tavazo, Maryam; Vakili, Mohammad Reza; Shahbazi-Alavi, Hossein
ABSTRACT: Chitosan (CS) functionalized by citric acid has been used as an efficient catalyst for the preparation of 2, 4-diamino-5 H -[1]benzopyrano[2, 3- b ]pyridine-3-carbonitriles 5-(arylthio) or 5-[(arylmethyl)thio] substituted by a multicomponent reaction of salicylaldehydes, thiols and 2 equiv. of malononitrile under reflux condition in ethanol. Use of simple and readily available starting materials, excellent yields in short times, reusability of the catalyst and little catalyst loading are some of the important features of this protocol. The structure of CS functionalized by citric acid was confirmed by infrared spectroscopy (FT-IR), X-ray diffraction, thermogravimetric analysis and differential scanning calorimetry. GRAPHICAL ABSTRACT: